2000
DOI: 10.1039/b001916j
|View full text |Cite
|
Sign up to set email alerts
|

Surface acidity modifications induced by thermal treatments and acid leaching on microcrystalline H-BEA zeolite. A FTIR, XRD and MAS-NMR study

Abstract: Samples of beta-zeolite thermally treated at different temperatures and acid leached with diluted hydrochloric acid solution have been investigated by XRD, Al-27 MAS-NMR spectroscopy and FTIR spectroscopy. The results have been used to interpret the behaviour of the samples as catalysts for the acylation of 2-methoxy-naphthalene. It has been shown that the as prepared sample presents two types of extraframework species. These are identified as Al hydroxo-ions highly dispersed in the internal zeolite channels a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
47
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(54 citation statements)
references
References 34 publications
5
47
2
Order By: Relevance
“…broad absorption centred at 3670 cm -1 which could be assigned to another family of Al-OH groups, whose Al is at least partially connected to the BEA framework [46,50]. Isolated Al-OH groups characterized by a FT IR band at 3785 cm -1 and due to extraframework (EF) Al, were detected for sample 1, having the highest Al content.…”
mentioning
confidence: 95%
See 3 more Smart Citations
“…broad absorption centred at 3670 cm -1 which could be assigned to another family of Al-OH groups, whose Al is at least partially connected to the BEA framework [46,50]. Isolated Al-OH groups characterized by a FT IR band at 3785 cm -1 and due to extraframework (EF) Al, were detected for sample 1, having the highest Al content.…”
mentioning
confidence: 95%
“…FT IR analysis was carried out to investigate the acidic character of the prepared catalysts [46][47][48][49]. In the hydroxyl region of the spectra, recorded after outgassing at 500°C (spectra not reported) several common features appear for samples 1 and 8 (calcined samples):…”
Section: -Ft Ir Investigation Of Zeolite Aciditymentioning
confidence: 99%
See 2 more Smart Citations
“…The three ordered polytypes are designated frameworks A, B, and C [19,20]. Polytype A is tetragonal (space group P4 1 22 or P4 3 It has been reported that thermal and hydrothermal treatments induce chemical and structural modifications in beta zeolites, for instance Trombetta et al [21] observed that thermal treatments can cause dealumination and formation of extraframework aluminium species. The ease of dealumination of beta may be due to the presence of defect sites close to the framework aluminium which promotes bond hydrolysis, nonetheless the microporous structure is not affected by the loss of aluminium [22].…”
Section: Introductionmentioning
confidence: 99%